"Brute people and the miserable poor" also fought. The indigenous people of Huamanga in Independence (Revista revoluciones, 2021)
This research, on the one hand, analyzes the reasons and role of the Huamanga indigenous people in the process of Independence. On the other hand, the meaning of the establishment of the republican administration for the natives. Through the review of a vast documentation we consider that the reasons for the rejection of the viceroyalty was the implementation of the Bourbon reforms and the war contributions in a context of poverty, rains, droughts and diseases. The indigenous people participated in the battlefields, formed militias, supplied the war and spread the information. However, in the republican government, they were relegated: they lost their identity diversity, they suffered the prohibition of festivities, territorial modifications and prolonged litigation.
Keywords: Indigenous; Huamanga; viceroyalty; Independence; Republic